Biomimetic Electronic Devices for Measuring Bacterial Membrane Disruption. Issue 39 (16th August 2018) - Pitsalidis, Charalampos; Pappa, Anna‐Maria; Porel, Mintu; Artim, Christine M.; Faria, Gregorio C.; Duong, Duc D.; Alabi, Christopher A.; Daniel, Susan; Salleo, Alberto; Owens, Róisín M.
Abstract: Antibiotic discovery has experienced a severe slowdown in terms of discovery of new candidates. In vitro screening methods using phospholipids to model the bacterial membrane provide a route to identify molecules that specifically disrupt bacterial membranes causing cell death. Thanks to the electrically insulating properties of the major component of the cell membrane, phospholipids, electronic devices are highly suitable transducers of membrane disruption. The organic electrochemical transistor (OECT) is a highly sensitive ion‐to‐electron converter. Here, the OECT is used as a transducer of the permeability of a lipid monolayer (ML) at a liquid:liquid interface, designed to read out changes in ion flux caused by compounds that interact with, and disrupt, lipid assembly. This concept is illustrated using the well‐documented antibiotic Polymixin B and the highly sensitive quantitation of permeability of the lipid ML induced by two novel recently described antibacterial amine‐based oligothioetheramides is shown, highlighting molecular scale differences in their disruption capabilities. It is anticipated that this platform has the potential to play a role in front‐line antimicrobial compound design and characterization thanks to the compatibility of semiconductor microfabrication technology with high‐throughput readouts. Abstract : Biomimetic electronic devices for measuring bacterial membrane disruption provide a new route for the design and screening of novel antibacterial compounds. A monolayer of phospholipids placed at a liquid–liquid interface blocks gating of the poly(3‐hexylthiophene‐2, 5‐diyl)‐based organic electrochemical transistor. This allows quantitative measurement of compounds that permeabilize the lipid layer, as they restore gating.